Political Advertising in the 2014 European Parliament Elections
XII, 243 p. 11 illus.
Keywords: This timely publication offers a fresh scholarly assessment of political advertising across the EU, as well as an insight into differing political and regulatory systems related to political advertising in the individual member states. With a detailed focus on the images and communication styles that characterised the 2014 European Parliament election campaign, this edited collection evaluates political advertising across the EU using empirical data to compare and contrast styles and approaches in different members. This work allows the authors to offer an important evaluation of the similarities and differences in the posters and broadcasts used to win public support in the 2014 campaign at the time of the great European recession and financial crisis, specifically looking at the place of posters and video commercials. This book will appeal to researchers and students of political communication, political science, history, European studies as well as candidates and campaign workers who want a more comprehensive understanding of the representation of Europe in political adverts at the 2014 elections.